Double‐blind, randomized crossover study of intravenous infusion of magnesium sulfate versus 5% dextrose on depressive symptoms in adults with treatment‐resistant depression. Issue 3 (29th December 2016) - Mehdi, Syed M. A.; Atlas, Steven E.; Qadir, Sidra; Musselman, Dominique; Goldberg, Sharon; Woolger, Judi M.; Corredor, Raul; Abbas, Muhammad H.; Arosemena, Leopoldo; Caccamo, Simone; Campbell, Carmen S. G.; Farooqi, Ashar; et al.
Abstract : Aim: Treatment‐resistant depression patients are more likely to suffer from comorbid physical and mental disorders, experience marked and protracted functional impairment, and incur higher health‐care costs than non‐affected individuals. Magnesium sulfate is a treatment option that may offer great potential for patients with treatment‐resistant depression based on prior work in animals and humans. Methods: Twelve subjects with mild or moderate treatment‐resistant depression were randomized into a double‐blind crossover trial to receive an infusion of 4 g of magnesium sulfate in 5% dextrose or placebo infusion of 5% dextrose with a 5‐day washout in between the 8‐day intervention period. Subjects were assessed before and after the intervention for serum and urine magnesium, lipid panel, the Hamilton Rating Scale for Depression, and the Patient Health Questionnaire‐9. Results: We found a difference in serum magnesium from day 2 to 8 (pre‐infusion) ( P  < 0.002) and from baseline to day 8 ( P  < 0.02). No changes were noted on the Hamilton Rating Scale for Depression or the Patient Health Questionnaire‐9 24 h post‐treatment, but as serum magnesium increased from baseline to day 7, the Patient Health Questionnaire‐9 decreased from baseline to day 7 ( P  = 0.02). Conclusion: Magnesium sulfate did not significantly affect depression 24 h post‐infusion, but other results were consistent with the literature. The association between changes in serum magnesium and the Patient Health Questionnaire‐9 supports the idea that magnesium sulfate may be used to address treatment‐resistant depression, an ongoing medical challenge.